2023
DOI: 10.1071/rj22040
|View full text |Cite
|
Sign up to set email alerts
|

In search of sustainable livestock management in the Dry Chaco: effect of different shrub-removal practices on vegetation

Abstract: Increasing shrub density hinders cattle raising in central Argentina rangelands. While roller-chopping and hand-cutting are used to remove shrubs and make land accessible for cattle grazing, studies on the effects of these practices on ecosystem composition, structure and functioning are scarce. We assessed the impact of shrub removal on (a) vegetation cover, composition, species richness and diversity and (b) green biomass and seasonal phenological dynamics. We used a randomised design with three treatments (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…These activities, promoted by the establishment of the European civilizations during the past four centuries, have strongly transformed the ecosystem structure (Ad amoli et al, 1990;Karlin et al, 2013). Recent studies showed that Dry Chaco woodlands provide key ecosystem services such (1) carbon sequestration (Bonino, 2006;García et al, 2017;Guzm an et al, 2021;Nosetto et al, 2020), (2) temperature regulation (García et al, 2017;Houspanossian et al, 2013;Nosetto et al, 2020), and (3) biodiversity conservation (Coria et al, 2015(Coria et al, , 2017Weiler et al, 2020).…”
Section: Region Landscape and Impoundmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…These activities, promoted by the establishment of the European civilizations during the past four centuries, have strongly transformed the ecosystem structure (Ad amoli et al, 1990;Karlin et al, 2013). Recent studies showed that Dry Chaco woodlands provide key ecosystem services such (1) carbon sequestration (Bonino, 2006;García et al, 2017;Guzm an et al, 2021;Nosetto et al, 2020), (2) temperature regulation (García et al, 2017;Houspanossian et al, 2013;Nosetto et al, 2020), and (3) biodiversity conservation (Coria et al, 2015(Coria et al, , 2017Weiler et al, 2020).…”
Section: Region Landscape and Impoundmentsmentioning
confidence: 99%
“…At the patch scale (1-10 m 2 ), infiltration excess overland flows can occur under intensive rainfall events from bare soil patches. This patch-scale runoff usually infiltrates into soil under vegetated patches where infiltration rate is greater (Guzm an et al, 2021;Karlin et al, 2019;Kunst et al, 2003;Magliano, Breshears, et al, 2015;Magliano et al, 2016). The interconnected bare soil patches and cattle movement and trampling along the landscape create the necessary connectivity to transport water for long distances (on the order of kilometers).…”
Section: Effect Of Cattle Transit and Trampling On The Landscapementioning
confidence: 99%
See 1 more Smart Citation